Analisis Karakteristik Ibu Dengan Tingkat Pengetahuan Ibu Tentang Imunisasi Pentavalen - Farida Kartini; Herlin Fitriani K. (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2016)
Background: Immunization of pentavalent is very important for the children who aim to protect children from transmission of diphtheria, pertussis, tetanus, hepatitis B and diseases caused by haemaphilus influenza B.Objective: This study aim to analyze the characteristics of mother with the level of knowledge about pentavalentimmunization.Methods: Method was an analytic study with a sample of 48 mothers. Sampling technique with total sampling. Datacollection using closed questionnaire. Data analysis using chi square and kendall’s tau analysis.Results: Data were obtained through questionnaire. Analysis of the data used univariate analysis. Chi square testresults between maternal age and maternal education level with maternal knowledge about pentavalent immunization respectively with p = 0,043 and p = 0,032. Kendall’s test between mother job stance and mother’s knowledgeabout pentavalent immunization schedule with mother’s knowledge level about pentavalent immunization respectively with p = 0,656 and p = 0,830.Conclusions: There was a relationship between maternal age and employment status with mother’s level of knowledge about pentavalent immunization. However, there was no relationship between maternal employment statusand mother’s knowledge about immunization schedule with mother’s knowledge level about pentavalent immunization.Keywords: child, level of knowledge, immunization, pentavalent, pentabio